Paeonol Attenuates Cigarette Smoke-Induced Lung Inflammation by Inhibiting ROS-Sensitive Inflammatory Signaling - Meng-Han Liu; An-Hsuan Lin; Hung-Fu Lee; Hsin-Kuo Ko; Tzong-Shyuan Lee; Yu Ru Kou (Hindawi Limited, 2014)
Cigarette smoking causes persistent lung inflammation that is mainly regulated by redox-sensitive pathways. We have previously reported that cigarette smoke (CS) activates reactive oxygen species- (ROS-) sensitive mitogen-activated protein kinases (MAPKs)/nuclear factor-κB (NF-κB) signaling leading to induction of lung inflammation. Paeonol, the main phenolic compound present in the Chinese herb Paeonia suffruticosa, has antioxidant and anti-inflammatory properties. However, whether paeonol has similar beneficial effects against CS-induced lung inflammation remains unclear. Using a murine model, we showed that chronic CS exposure for 4 weeks caused pulmonary inflammatory infiltration, increased lung vascular permeability, elevated lung levels of chemokines, cytokines, and 4-hydroxynonenal (an oxidative stress biomarker), and induced lung inflammation; all of these CS-induced events were suppressed by chronic treatment with paeonol. Using human bronchial epithelial cells (HBECs), we demonstrated that cigarette smoke extract (CSE) sequentially increased extracellular and intracellular levels of ROS, activated the MAPKs/NF-κB signaling, and induced interleukin-8 (IL-8); all these CSE-induced events were inhibited by paeonol pretreatment. Our findings suggest a novel role for paeonol in alleviating the oxidative stress and lung inflammation induced by chronic CS exposure in vivo and in suppressing CSE-induced IL-8 in vitro via its antioxidant function and an inhibition of the MAPKs/NF-κB signaling.